2012
DOI: 10.1177/1069072712450010
|View full text |Cite
|
Sign up to set email alerts
|

Career Thoughts, Indecision, and Depression

Abstract: This study investigated the relationships among dysfunctional career thoughts and career indecision with respect to symptoms of depression. Such information could be useful to counselors in identifying individuals at the outset of career counseling who may be experiencing emotional distress from life stressors in addition to career stress. One-hundred fifty-eight college students enrolled in a career development course completed measures of dysfunctional career thoughts, an occupational alternative question, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 24 publications
2
42
0
3
Order By: Relevance
“…For example, Brown and Brooks recommended that career counselors assess for clients' psychological distress and cognitive clarity at the outset of career counseling. In addition, others (e.g., Walker & Peterson, 2012) have suggested that when career counselors are administering career assessments, it is important for them to attend to the role of psychological distress when scoring and interpreting results. Heightened levels of distress are likely to affect responses to a variety of career-related questions.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Brown and Brooks recommended that career counselors assess for clients' psychological distress and cognitive clarity at the outset of career counseling. In addition, others (e.g., Walker & Peterson, 2012) have suggested that when career counselors are administering career assessments, it is important for them to attend to the role of psychological distress when scoring and interpreting results. Heightened levels of distress are likely to affect responses to a variety of career-related questions.…”
Section: Implications For Practicementioning
confidence: 99%
“…To address the relative lack of attention directed toward understanding the linkages between career development and mental health symptomatology DECEMBER 2019 • VOLUME 67 (e.g., Juntunen, 2006;Saunders, Peterson, Sampson, & Reardon, 2000;Walker & Peterson, 2012), career counselors also are encouraged to develop psychoeducational workshops that explicate the relationships among mental health and various career-related constructs and the pursuit of career development opportunities. For example, career counselors are well positioned to illuminate some of the ways that career development tasks (e.g., choosing a major, pursuing a work-based learning opportunity, deciding to participate in mock interviews, or seeking assistance in résumé or cover letter writing) may be affected by psychological distress.…”
Section: Implications For Practicementioning
confidence: 99%
“…Previous research has indicated that depression may lead to higher levels of dysfunctional attitudes, negative automatic thoughts, and cognitive distortions such as loneliness, feeling trapped, and hopelessness about the future (Eaves & Rush, 1984;Murgai & Sathyavathi, 1987). Research also indicates a link between depression and the ability to effectively engage in career decision making (Rottinghaus, Jenkins, & Jantzer, 2009;Saunders, Peterson, Sampson, & Reardon, 2000;Walker & Peterson, 2012). Walker and Peterson (2012) suggested that "venturing into the realm of mental health issues has the potential to reveal severe or chronic pathological states or even suicide ideation.…”
Section: Connection Between Career and Mental Health Concernsmentioning
confidence: 99%
“…Two of these factors include (a) the degree of indecision or uncertainty with respect to a career choice and (b) the extent of dissatisfaction with the choice. These factors are collectively referred to as the career decision state (Bullock-Yowell et al, 2011;Walker & Peterson, 2012). Osipow (1999) stated that making a career decision can be one of the more stressful and anxiety-provoking life experiences, which could lead to career decision-making difficulties.…”
Section: Career Decision Statementioning
confidence: 99%